CRISPR/Cas9: A tool for immunological research. Issue 4 (26th February 2018) - Hochheiser, Katharina; Kueh, Andrew J; Gebhardt, Thomas; Herold, Marco J
Abstract: The CRISPR/Cas9‐system was originally identified as part of the adaptive immune system in bacteria and has since been adapted for the genetic manipulation of eukaryotic cells. The technique is of particular value for biomedical sciences, as it enables the genetic manipulation of cell lines and primary cells as well as whole organisms with unprecedented ease and efficiency. Furthermore, the CRISPR/Cas9‐technology has the potential for future therapeutic applications in the clinic. Here, we discuss the use of CRISPR/Cas9 for the genetic modification of haematopoietic cells and the generation of mouse models for immunological research. Additionally, we explain how the technique can be applied as a screening‐tool to identify genes involved in different immunological processes. Moreover, we will talk about recent extensions of using the CRISPR/Cas9 technology, such as a transcriptional activator or repressor. Finally, we discuss the first clinical trials that use CRISPR/Cas9 and discuss potential future applications. Abstract : The review article by Hochheiser et al. discusses the use of the CRISPR/Cas9 technology for the genetic manipulation of haematopoietic cells and whole animals, and its potential application in the clinic.